Selection of the Binding Object on the Current Image Formed by the Technical Vision System Using Structural and Geometric Features - Sotnikov O.; Sivak V.; Pavlov Ya.; Нashenko S.; Borysenko T.; Torianyk D. (Problems of the Regional Energetics)
The purpose of the article is to substantiate the possibility of selecting objects in the image generated by the technical vision system of an unmanned aerial vehicle by using structural and geometric features. This goal is achieved based on the analysis of the distribution of fractal dimension, which characterizes the structural properties of images, taking into account the object content, and the size of the area of the selection object. The solution to the first problem is based on the formation of histograms of fractal dimension depending on the number of objects in the image and identifying the features by which the object is selected. The solution to the second problem is based on developing an approach to reducing the object content of images by making it noisy. The noise parameters at which signs of object selection appear in the histograms of the distribution of fractal dimensions are determined. The range of fractal dimension defined. The solution to the third problem is based on specifying the selection object by its area. The most significant result is the identified values of fractal dimension ranges depending on the object content of the image, as well as experimentally established noise parameters to identify the necessary features in histograms of fractal dimensions. The significance of the work lies in solving the problem of selecting a reference object on images of heterogeneous object composition. This made it possible to reduce significantly the computational complexity of selecting objects in images.